The Influence Of Tax Socialization And Literacy On Land And Building Taxpayer Compliance (A Case Study At The Sub-District Office Of Karang Tengah, Tangerang) - Wahyudin, Dian; Chairunnisa, Meira Ayu (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The aim of this research is to determine the extent of the influence of tax socialization and literacy on taxpayer compliance at the Sub-District Office of Karang Tengah, Tangerang. This quantitative research utilized data collection through literature review and field studies conducted via questionnaires, involving a sample of 96 respondents. The research employed various techniques, including Instrument Testing (validation, reliability, and descriptive analysis), Classical Assumption Testing (Normality, Heteroscedasticity, and Multicollinearity), and Hypothesis Testing (Multiple Linear Regression Analysis, t-test, F-test, and coefficient of determination (R2) using SPSS version 25. The results revealed a significant influence between tax socialization and literacy variables on land and building taxpayer compliance at the Sub-District Office of Karang Tengah, Tangerang. The coefficient of determination (R2) indicated that the combined influence of tax socialization and literacy on taxpayer compliance is 24.5%. This means that 24.5% of taxpayer compliance can be explained by tax socialization and literacy variables. The t-test results showed that tax socialization has a significance value of 0.008 < 0.05, indicating that tax socialization has a partial influence on taxpayer compliance. Similarly, tax literacy has a significance value of 0.019 < 0.05, indicating that tax literacy has a partial influence on taxpayer compliance. The F-test yielded a significance value of 0.000 < 0.05, showing that tax socialization and literacy variables simultaneously influence land and building taxpayer compliance at the Sub-District Office of Karang Tengah, Tangerang.